Membangun Gender Partnership di Era 5.0 Perspektif QS. Al-Hujurat ayat 13 dan QS. Al-An’am ayat 165 - A'la, Nusrotul; Aini, Adrika Fithrotul; Irsyadi, Najib (UIN Sultan Syarif Kasim Riau, 2023)
The Introduction to gender and their respective roles is crucial from an early age. Islam does not differentiate between the roles of women and men. The continuity of the relationship between men and women must be maintained within the corridor of Islamic law without gender intimidation. This article aims to build gender partnership in Era 5.0 based on the Qur'an, Surah Al-Hujurat, verse 13, and Surah Al-An'am, verse 165. Thus, understanding gender partnerships can be one way to address gender disparities, enhance well-being, and improve Human Resources (HR) quality. The research method used in this article is qualitative research in the form of a literature review based on sources such as books, articles, and works discussing gender partnerships. Data collection methods are conducted through a literature review of data obtained from various sources. The primary data sources are the Qur'an, Surah Al-Hujurat, and Al-An'am. From the study's results, it can be concluded that gender partnership means a condition where there is mutual understanding, respect, and cooperation with the different attitudes and strengths of the opposite sex. In efforts to build gender partnership in Era 5.0 according to the perspective of the Qur'an, Surah Al-Hujurat, verse 13, and Surah Al-An'am, verse 165, it is crucial to establish equal and humane rights for both women and men. This entails fully guaranteeing the rights of each gender and treating them well. Efforts to build gender partnerships include understanding and recognizing that men and women have different characteristics, paying attention to the gender division of labor, fostering good collaboration and coordination, mutual respect and non-discrimination, and offering differences in strategic needs for each gender. Abstrak: Pengenalan gender dan tugas masing-masing penting dimulai sejak dini. Agama Islam tidak membedakan peran antara perempuan dengan laki-laki. Kesinambungan hubungan laki-laki dan perempuan harus tetap terjaga dalam koridor syariat Islam tanpa adanya intimidasi gender. Artikel ini bertujuan untuk membangun kemitraan gender (gender partnership) pada Era 5.0 berdasarkan al-Qur’an surah Al-Hujurat ayat 13 dan surah Al-An’am ayat 165. Sehingga pemahaman tentang kemitraan gender mampu menjadi salah satu cara mengatasi kesenjangan gender, meningkatkan kesejahteraan dan kualitas Sumber Daya Manusia (SDM). Metode penelitian yang digunakan dalam artikel ini adalah penelitian kualitatif dengan bentuk studi pustaka berdasarkan sumber data dari buku, artikel, dan karya yang membahas kemitraan gender. Adapun metode pengumpulan data dilakukan melalui kajian literatur kepustakaan dari sumber data yang diperoleh. Sumber data primernya adalah al-Qur’an Surat Al-Hujurat dan Al-An’am. Dari hasil studi dapat ditarik hasil bahwa kemitraan gender berarti kondisi di mana terdapat rasa saling memahami, menghargai, dan bekerja sama dengan sikap dan kekuatan yang berbeda dari lawan jenis. Dalam upaya membangun kemitraan gender pada era 5.0 sesuai perspektif al-Qur’an surah Al-Hujurat ayat 13 dan surah Al-An’am ayat 165 menetapkan hak-hak perempuan dan laki-laki secara berimbang dan penuh dengan perikemanusiaan. Secara totalitas menjamin sepenuhnya hak-hak setiap gender dan memperlakukannya dengan baik. Upaya membangun kemitraan gender yaitu dengan memahami dan menyadari antara laki-laki dan perempuan memilki karakteristik yang berbeda, menaruh perhatian pada pembagian kerja gender, kolaborasi dan koordinasi yang baik, saling menghormati dan tidak membeda-bedakan, serta menawarkan perbedaan pada kebutuhan strategis masing-masing.